2015
DOI: 10.14807/ijmp.v6i1.251
|View full text |Cite
|
Sign up to set email alerts
|

Formalisation versus tacitness: keys for creating and sharing knowledge in innovative large organisations

Abstract: In the situated learning theory, we disclose the existence of some tensions that may arise from two opposite forces within a context of communities of practice: the need for formalisation (large enterprises) and tacitness (creativity and innovation). Our study focuses on how these tensions are dealt with in a case study of a Portuguese innovative large enterprise that has developed a knowledge strategy over the last decade.The keys for overcoming this risky confrontation are related to a combination of "knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Clark et al and Swan et al find that sharing knowledge is a learning and reflection process that provides opportunities for disciplines to reassess their stance [25,26]. Sousa and Gonzalez-Loureiro term this "knowledge in action" [27]. Sousa and Gonzalez-Loureiro, referring to Nonaka and Takeuchi [28], detail the knowledge sharing process as four modes; these are socialisation, externalisation, combination, and internalisation.…”
Section: Interdisciplinary Relationships Influence and Aspirationsmentioning
confidence: 99%
“…Clark et al and Swan et al find that sharing knowledge is a learning and reflection process that provides opportunities for disciplines to reassess their stance [25,26]. Sousa and Gonzalez-Loureiro term this "knowledge in action" [27]. Sousa and Gonzalez-Loureiro, referring to Nonaka and Takeuchi [28], detail the knowledge sharing process as four modes; these are socialisation, externalisation, combination, and internalisation.…”
Section: Interdisciplinary Relationships Influence and Aspirationsmentioning
confidence: 99%
“…Sousa and González-Loureiro (2015) noted that the high levels of creativity and innovation at organizational levels were associated with the need of managers and employees to participate and share knowledge. Sousa and González-Loureiro (2015) indicated that knowledge sharing and reuse were difficult for managers due to the availability and use of different mechanisms (such as documents, databases, intranets, KMS, communities of practices, and groupware).…”
Section: Wwwijcatcom 442mentioning
confidence: 99%